Pengaruh Minat Belajar, Fasilitas Belajar dan Keterlibatan Siswa Terhadap Hasil Belajar Pendidikan Agama Islam Kelas 4 SDN Kalimulya Depok - Yanti Damayanti; Chaira Saidah Yusrie; Yusi Suhartini (Pascasarjana IAI Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the influence of learning interest, learning facilities, and student engagement on the learning outcomes of Islamic Religious Education (PAI) in junior high schools. Learning interest is an essential factor that motivates students to be more active in the learning process. Adequate learning facilities also support the creation of a condcive learning environment. Student engagement, which includes active participation in classroom activities and interaction with teachers and peers, is identified as a key element in enhancing understanding and academic achievement.This research employs a quantitative approach using a survey method. Data were collected through questionnaires distributed to eighth-grade students in several junior high schools. The data were analyzed using multiple linear regression techniques to examine the relationships between these variables.The results of the study indicate that learning interest, learning facilities, and student engagement significantly and positively influence PAI learning outcomes. Learning interest has the most dominant effect compared to other variables. Based on these findings, it is recommended that schools improve learning facilities and encourage active student engagement in learning, as well as develop programs that can enhance students' learning interest. This study employs a quantitative approach using survey methods. Data were collected through questionnaires distributed to fourth-grade students in several junior high schools. Multiple linear regression analysis was conducted to examine the relationships between these variables. The findings indicate that learning interest, learning facilities, and student engagement positively and significantly affect PAI learning outcomes. Among these, learning interest has the most dominant influence.This study employs a quantitative approach using survey methods. Data were collected through questionnaires distributed to fourth-grade students in several junior high schools. Multiple linear regression analysis was conducted to examine the relationships between these variables. The findings indicate that learning interest, learning facilities, and student engagement positively and significantly affect PAI learning outcomes. Among these, learning interest has the most dominant influence. Based on these findings, it is recommended that schools enhance learning facilities, encourage active student engagement in the learning process, and develop programs to boost student learning interest.